Mayday over Wichita the worst military aviation disaster in Kansas history - Carter, D. W. (Charleston, SC History Press, 2013)
"On the cold Saturday morning of January 16, 1965, a U.S. Air Force KC-135 tanker carrying thirty-one thousand gallons of jet fuel crashedinto a congested African American neighborhood in Wichita, Kansas. When the fire and destruction finally subsided, forty-seven people--mostly African American children--were dead or injured, homes were completely destroyed and numerous families were splintered. As shocking as it may sound, the event was seemingly omitted from the historical record for nearly fifty years. Now, historian D. W. Carter examines the myths and realities of the crash while providing new insights about the horrific four-minute flight that forever changed the history of Kansas. "--
Includes bibliographical references (pages [133]-155) and index.
Keywords: African Americans; Natural Disasters; Military; Kansas -- Wichita; Kansas -- Sedgwick County